Eulophia myanmarica (Orchidaceae), a new species from Myanmar and notes on Geodorum densiflorum - Naive, Mark Arcebal K.; Hein, Khant Zaw; Kumar, Pankaj; Ormerod, Paul (Phytotaxa, 2022)
Eulophia myanmarica, a species new to science is herein described from Monywa District, Sagaing Region, Myanmar. The species superficially resembles E. andamanensis but differs significantly in having 5-veined petals and sepals, narrowly oblong dorsal sepal with acute, slightly cucullate apex, obliquely narrowly oblong-elliptic lateral sepals and obliquely triangular sidelobes of the labellum. Detailed morphological description, a colour plate, notes on phenology, distribution, and a provisional conservation assessment are provided below. With this discovery, Myanmar now holds a total number of 19 Eulophia species. Additionally, after merging the genus Geodorum under Eulophia, a new name is needed for Geodorum densiflorum, for which taxonomic notes have been provided.